"The True Practice is Theory": Edgar Bauer, Republicanism, and the Young Hegelians. Issue 4 (2nd October 2022) - Barbour, Charles
ABSTRACT: The recent past has witnessed a significant amount of new interest in the intellectual history of the Vormärz, or the period in German history immediately prior to the 1848 Revolutions, and especially in the theories of republicanism developed among those who are variously known as the Young, Left, or New Hegelians. At the same time, scholars have reopened the question of Marx's relationship with republicanism and the republican conception of freedom. But one figure who has been conspicuously overlooked in this context was arguably the most radical and revolutionary republican of the period: Edgar Bauer. This paper fills a gap in the extant literature by providing a survey of Edgar Bauer's work during the crucial years of 1841–1843. It shows that his position differed in important ways from that of his brother Bruno and explains the political stakes of his equally vehement attacks on the Christian state, on the one side, and its liberal opposition, on the other. It proposes that his position developed rapidly over the course of the three years in question, until he was finally arrested, put on trial, and imprisoned for insulting religious society, mocking the law, arousing dissatisfaction with the state, and offending the majesty of the king.